A Signature Pedagogy for Initial Teacher Education in Singapore. Issue 3 (3rd July 2019) - Tan, Charlene
ABSTRACT: This article focuses on the application of Shulman's signature pedagogies for initial teacher education through the example of a pre-service course that promotes multidimensional thinking skills in Singapore. Multidimensional thinking emphasizes the thought processes, attitudes and abilities needed to address complex issues and problems from multiple angles and approaches. The course objectives, content, assessment format and delivery mode are premised on and reflect Shulman's three dimensions of structures – surface, deep and implicit – as well as three kinds of pedagogies – uncertainty, engagement and formation. This illustrative case study from Singapore demonstrates the usefulness of the notion of signature pedagogies to help teacher educators design and enact learner- and learning-centered courses for pre-service teachers. Such courses transcend a narrow skills-based approach to advance the essential values, competencies and knowledge for initial teacher education in the 21st century.